A Safety Evaluation of a Nature-Identical l-Ergothioneine in Sprague Dawley Rats. (September 2016) - Marone, Palma Ann; Trampota, Jan; Weisman, Steven
L -(+) Ergothioneine is a naturally occurring thiol amino acid with antioxidant properties and potential benefits as a dietary supplement. Despite its century-old identification and wide distribution in human food, little is known of its mechanism of action and safety. The nature-identical biomimetic ofl -(+) ergothioneine, produced by Mironova Labs and supplied as Mironova (EGT+), has been investigated in the present studies for its mutagenic and toxicologic potential. In a plate incorporation and preincubation assay with Salmonella typhimurium strains TA98, 100, 1, 535, and 1, 537 and Escherichia coli WP2uvrA strain, at dose concentrations of 1.58, 5, 15.8, 50, 158, 500, 1, 580, and 5, 000 μg/plate with and without metabolic activation, no cytotoxicity or mutagenicity was observed. Following a preliminary 28-day study, a repeated dose 90-day gavage study at dose levels of 0, 400, 800, and 1, 600 mg/kg body weight (bw)/d in Sprague Dawley rats, in which dose-proportional systemic absorption was confirmed by plasma analysis, no adverse clinical, body weight/gain, food consumption and efficiency, clinical pathology, or histopathological changes associated with the administration of the nature-identical ergothioneine were observed. In conclusion, EGT+ administered over 90 days was well tolerated with a no adverse effect level at 1, 600 mg/kg bw/d, the highest dose tested for male and female rats. In addition, the nature-identical test substance, EGT+ was not mutagenic in a bacterial reverse mutation assay at plate concentrations of up to 5, 000 μg/mL in the presence or absence of metabolic activation.